(3GdSMGH hGdeWQ hGdTLQs - (3GHf OQjO , CHh HcQ eMeO Hf GdMSf Hf OQjO GdCROj, GHf OQjO,J (B321 (3g` s
(3ChdgG (B:s
(3MOKfG CHh YHjOG ddg GdMSjfi Hf NGdhjg bGd bGd CHh HcQ eMeO Hf GdMSjf Hf OQjO fHJOC HMeO Gddg Ydi BdGFg hfNJe HGdUdGI Ydi NGJe CfHjGAg gPG cJGH LeYfG ajg eG PcQJg GdYQH ai LGgdjJgG s
(3BNQgG (B:s
(3ef hUa GdeWQ hGdSMGH abGdJ ZKfG eG TFfG Ci CUGHfG GdZjK hGddg CYde HGdUhGH Je cJGH GdeWQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B80 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B189 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B32s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3CdeGfjG s
Keywords: (3GddZIs